2010
DOI: 10.3109/0886022x.2010.502606
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of role of doxycycline (a matrix metalloproteinase inhibitor) on renal functions in patients of diabetic nephropathy

Abstract: This study was conducted to see the effect of doxycycline on renal functions, especially proteinuria, in patients of diabetic nephropathy (DN). The study included 40 clinically proven adult patients of DN. All patients were on stable doses of angiotensin-converting enzyme inhibitors (ACEIs) and or angiotensin receptor blockers (ARBs) for 2 months before the study. The patients were divided into two groups of 20 patients each. Group A patients were maintained on stable dose of ACEIs and/or ARBs, whereas Group B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Furthermore, doxycyline at 2.0 mg/kg attenuates lung injury induced by LPS, doxycycline-resistant S. pneumoniae and bleomycin; and reduces inflammation in a model of asthma [4,5,14]. In humans, doxycycline has been used in the treatment of lymphangioleiomyomatosis (LAM) [15,16] and decreases proteinuria in diabetic nephropathy [17], although it was found to have no effect in osteoarthritis [18]. Clearly, doxycycline has anti-inflammatory properties that are independent of its antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, doxycyline at 2.0 mg/kg attenuates lung injury induced by LPS, doxycycline-resistant S. pneumoniae and bleomycin; and reduces inflammation in a model of asthma [4,5,14]. In humans, doxycycline has been used in the treatment of lymphangioleiomyomatosis (LAM) [15,16] and decreases proteinuria in diabetic nephropathy [17], although it was found to have no effect in osteoarthritis [18]. Clearly, doxycycline has anti-inflammatory properties that are independent of its antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Aggarwal et al demonstrated that compared with angiotensin-converting enzyme inhibitors (ACEIs) and or angiotensin receptor blockers (ARBs), doxycycline (an inhibitor of MMP) can effectively reduce proteinuria in adult patients with DN, but unfortunately it is effective only for a short duration, i.e. , less than 12 weeks [143]. …”
Section: Mmps and Diabetic Nephropathymentioning
confidence: 99%
“…MMP9 is another protease which has been investigated with respect to its role in the DN with mixed variable results and contradictions. It is of interest to note that non-specific pharmacological inhibition of MMP9 with doxycycline were found to be associated with amelioration of renal injury [143]. In addition, it is also reported that Simvastatin protects kidney damage of diabetic rat through the suppression of MMP9 expression [147].…”
Section: Mmps and Diabetic Nephropathymentioning
confidence: 99%
“…The mechanism remains unclear. [189] [190][191][192][193][194][195][196] MMP-plays important role in development of diabetic nephropathy. [193,194] Dysregulation in NGAL, MMP-9 aand MMP2 is noted in type1 diabetes.…”
Section: Mechanismmentioning
confidence: 99%